Effect of ceramic reinforcements on microwave sintered metal matrix composites. Issue 1 (2nd January 2018) - Ashwath, P.; Xavior, M. Anthony
ABSTRACT: Metal matrix composites (MMCs) using Aluminum Alloy 2900 and 2024 as matrix material with silicon carbide and alumina as reinforcement have been fabricated through powder metallurgy route for investigation. The average particle size of matrix metal and reinforcement material considered in this research is 10 µm. AA-SiC and AA-Al2 O3 composites with 3, 6, and 9 weight percentage (wt%) of SiC and Al2 O3 are fabricated. The Rockwell hardness and Compressive strength of AA-SiC and AA-Al2 O3 composites were found to increase with an increase in the wt% of reinforcement when the samples were microwave sintered. AA 2024 with 6 wt% Al2 O3 reinforced MMCs samples were exhibiting improved hardness results, strength behavior, and stress-strain behavior when the samples are microwave sintered. AA 2900 with 6 wt% Al2 O3 exhibited good ductility and formability properties. Good Microstructural bonding was observed in the MMCs, which is attributed to finer Al2 O3 particulate used as reinforcement and the microwave sintering.